Traces of Collective Memory: Exploring the Shared Meanings of the Zeve Artyrs’ Memorial - Uğur Bozkurt; Mehmet Karasu (Current Perspectives in Social Sciences)
In this study, we examined the Zeve Martyrs’ Memorial as a collective memory builder and shaper, exploring the content and structure of shared meanings surrounding the memorial. A total of 481 university students participated in the study (Female = 341; Male = 140). To explore the content and structure of representations related to the Zeve Martyrs’ Memorial, participants were instructed to spontaneously write down the first four words that came to mind when prompted with “the Zeve Martyrs’ Memorial.” They then ranked these words based on free association, providing hierarchical association data. The word association test data were subjected to prototype analysis and similarity analysis using the IRAMUTEQ program. The results of this mixed-design study reveal that the shared meanings associated with the Zeve Martyrs’ Memorial are as follows: a) underscore the endurance of the tragedy through national and religious symbols; b) accentuate negative experiences within the tragedy; and c) exhibit a greater focus on intragroup processes than intergroup processes. Thorough examination of the personal- and group-level functions of these shared meanings is given. Both sets of results contribute to the literature on social representation and collective memory and underscore the importance of recontextualizing the Zeve Martyrs’ Memorial to enrich human experience.